Public-private partnership/concessions contracts of listed portuguese firms: the role of firm-specific determinants - Lopes, A.I.; Tânia Caetano ("XXIV Jornadas Luso-Espanholas de Gestão Científica: Contributo da Gestãopara a Sustentabilidade das Organizações e da Sociedade", 2014)
This research examines the firm-specific determinants of listed Portuguese firms having Public Private Partnerships -Concessions Contracts (PPP-CC). Based on accounting standards and other legislation regarding PPP-CC, a set of firm characteristics was tested in order to find those linked to the probability of having those arrangements. The research covers a period of four years, between 2008 and 2011, under which 132 firm-year observations are analyzed using a binary logistic regression model. The findings show that, as expected, larger firms, more leveraged and with higher level of Working Capital have more probability of having PPP-CC. Asymmetric Information, which was expected to have a negative impact, has shown to affect positively the probability of having PPP-CC. As expected, growing opportunities is not a distinguish characteristic. Several other characteristics were not supported. This research contributes to the scarce but growing literature on services concessions arrangements.